2022
DOI: 10.1021/acssuschemeng.2c02613
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Switchable Polymer: Uniting Deep Eutectic Solvents with Poly(N-isopropylacrylamide) and Poly(N-vinyl caprolactam)

Abstract: As analogs of ionic liquids (ILs), deep eutectic solvents (DESs) have attracted considerable attention as benign liquid formulations in the fabrication of polymeric materials because of the numerous advantages and functionalities of these liquid formulations, along with their ability to satisfy the principle of sustainability. Herein, the effectiveness of choline chloride (ChCl)-based DESs as a cosolvent was studied in the development of a versatile platform for regulating the thermal behavior of poly(N-isopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…[51][52][53] DESs have emerged as a sustainable solvent media for several applications. 54,55 Previous work has also been explored to evaluate the stability of proteins like keratin, horseradish peroxidase, and laccase in the activity and oligomerization of rutin, a-chymotrypsin in [Ch]Cl-urea and [Ch]Cl-Gly DESs, which concluded that the stability of the proteins was conserved in both DESs. 26,48,[56][57][58] Esquembre et al 59 have demonstrated that [Ch]Cl-urea caused destabilization of the lysozyme, whereas [Ch]Cl-Gly provided stability to the protein, and similar results for[Ch]Cl-Gly have been provided by Fernandez et al 26 as the structure of the lysozyme was retained at higher concentrations in the presence of [Ch]Cl-Gly.…”
Section: Thermodynamic Analysis Of Hb In the Presence Of Dessmentioning
confidence: 99%
“…[51][52][53] DESs have emerged as a sustainable solvent media for several applications. 54,55 Previous work has also been explored to evaluate the stability of proteins like keratin, horseradish peroxidase, and laccase in the activity and oligomerization of rutin, a-chymotrypsin in [Ch]Cl-urea and [Ch]Cl-Gly DESs, which concluded that the stability of the proteins was conserved in both DESs. 26,48,[56][57][58] Esquembre et al 59 have demonstrated that [Ch]Cl-urea caused destabilization of the lysozyme, whereas [Ch]Cl-Gly provided stability to the protein, and similar results for[Ch]Cl-Gly have been provided by Fernandez et al 26 as the structure of the lysozyme was retained at higher concentrations in the presence of [Ch]Cl-Gly.…”
Section: Thermodynamic Analysis Of Hb In the Presence Of Dessmentioning
confidence: 99%
“…Additionally, lactic acid as HBD has shown a substantial impact on the phase transition of PVCL polymer, which can be attributed to hydrogen bond formation between lactic acid and the hydration layer of PVCL and the subsequent formation of sponge-like PVCL mesoglobules. 85,86 Moreover, this investigation can also be confirmed by the lactic acid chemical structure, which possesses magnificent capability to interact with the surrounding water molecules pertaining to the presence of hydroxyl and carboxyl groups. Disruption of water and hydrogen bonding interactions resulted in the hydrophobic collapse of the PNIPAM.…”
Section: The Influence Of Dess On the Phase Transition Behavior Of Sm...mentioning
confidence: 55%
“…In another study, the influences of ChCl-based DESs (ChCl:urea, ChCl:EG, and ChCl:LA) on the thermal phase behavior of PNIPAM were studied by steady-state fluorescence spectroscopy, DLS, FTIR spectroscopy, thermal fluorescence spectroscopy, and UV-visible absorption spectroscopy. 86 Fig. 8 schematically illustrates conformational changes and aggregation behaviors in PNIPAM and PNIPAM-DES aqueous solution.…”
Section: The Influence Of Dess On the Phase Transition Behavior Of Sm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer response to different stimuli remains a hot research topic for those designing polymers that mimic biological molecules . Researchers have already prepared polymers that respond to light, pH, temperature, magnetic and electric fields, ultrasound, osmolytes, ionic liquids, chemical agents, and solvents. Phase separation is the most common polymer response to external stimuli and occurs due to modulations of interactions between polymeric chains and solvents without changing the chemical configuration of the polymer. Natural processes play an essential role in bridging the gap between the biological realm and artificial systems. Responses to external stimuli are well demonstrated in nature by the foliage folding of plants in response to touch, the color changes of chameleons, the movements of sunflowers, venus flytraps, and the opening of morning glory in sunlight. ,, These responses have encouraged studies on polymer responses to biochemical agents, proteins, enzymes, glucose, and antigens, and results to date indicate these approaches have huge in vivo applications. …”
Section: Introductionmentioning
confidence: 99%